CYBER NOTARY IN INDONESIA: REVIEW DURING THE COVID-19 PANDEMIC AND THE URGENCY OF POST-PANDEMI COVID-19 LEGAL REGULATIONS - Desia Rakhma Banjarani; Neisa Ang Rum Adisti; Isma Nuriilah; Helena Primadianti (Warmadewa Press, 2023)
The role of the notary is required to be able participate in the development of technology and information, because in an electronic transaction is very possible for the intervention of a notary as a trusted third party. It is very inappropriate if the notary still uses conventional methods in providing services, because speed, timeliness and efficiency are needed by the parties. So, the research problem can be formulated as follows: How is the development of cyber notary in Indonesia? Why is cyber notary regulation so urgent in Indonesia after the Covid 19 Pandemic? In this research, the authors objectively describe cyber notaries in Indonesia. This research is normative research with the authors arranged descriptively through a qualitative approach. There are no specific legal provisions that regulate cyber notaries, while the use of cyber notaries is increasingly urgent during the pandemic era, such as the Covid 19 Pandemic. However, due to the absence of regulations governing cyber notaries, there were several problems in implementing cyber notaries during the Covid 19 Pandemic era. Therefore, after the Covid 19 Pandemic there was a need for special regulations governing cyber notaries. This is because the Notary Office Law, which has been the legal basis for implementing cyber notaries, actually has several articles and provisions that hinder the implementation of cyber notaries.